Wear Behavior and FESEM Analysis of LM 25 Alloy MMHCs Reinforced with FE3O4 and Gr by Utilizing Taguchi's Technique. (19th July 2022) - Gokilakrishnan, G.; Sathishkumar, R.; Sivakumar, N. S.; Kaliappan, S.; Sekar, S.; Patil, Pravin P.; Subbiah, Ram; Yuvaraj, K. P.; Tadesse, Feleke Worku
Abstract : The current research is concerned with the production of an LM25-FE3O4—Gr metal matrix hybrid composites (MMHCs) and the analysis of its dry sliding wear conditions. The hybrid composites were made out of 3 wt% Fe3O4 and 4 wt% Gr particles with a mesh size of 200 meshes and were made using the stir casting method. Wear test on Taguchi's L9 orthogonal arrays employs three process parameters: load, sliding velocity, and distance, each changed for three levels on a pin-on-disc tester position. The wear behavior of hybrid composite was investigated using loads of 20 N, 40 N, and 60 N; velocities of 2 m/s, 4 m/s, and 6 m/s; and distances of 1, 000 m, 2, 000 m, and 3, 000 m. The major parameters were developed utilizing the signal-to-noise ratio by selecting "smaller-is-better" wear rates and COF features. FESEM was used to look at the worn surfaces of the composite specimen in order to determine the wear mechanism. Wear properties are enhanced in materials having aluminium hybrid metal matrix composites. According to the ANOVA table, the load parameter has the greatest impact on wear resistance and coefficient of friction, with maximum load values of 35.64 N and 5.782 N, respectively.